Adapting to new forms of teaching in the “Learning in Depth” program (Praxis Educativa, 2013)
It has long been argued that being educated entails satisfying two criteria: first, one must know many things about the world and, second, that one must know something in significant depth. There have been a number of proposals for attaining the depth criterion, none of them either clear or clearly successful. A curriculum innovation from Canada called “Learning in Depth” is a simple and practicable program for ensuring depth learning for all students, and it seems to merit wider experimental implementations. It also requires somewhat new forms of teaching.
Keywords: learning; depth; teaching; curriculum